2014
DOI: 10.1016/j.bpj.2014.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Organization of Troponin on Cardiac Muscle Thin Filaments in the Relaxed State

Abstract: Muscle contraction is regulated by troponin-tropomyosin, which blocks and unblocks myosin binding sites on actin. To elucidate this regulatory mechanism, the three-dimensional organization of troponin and tropomyosin on the thin filament must be determined. Although tropomyosin is well defined in electron microscopy helical reconstructions of thin filaments, troponin density is mostly lost. Here, we determined troponin organization on native relaxed cardiac muscle thin filaments by applying single particle rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 54 publications
(106 reference statements)
6
56
1
Order By: Relevance
“…4 A and E), which is broadly consistent with a previous model for the skeletal muscle thin filament (Model 2 of Knowles et al) [12] and the recently published model of cardiac thin filament in the relaxed state using a single-particle reconstruction technique [23]. It is also in general agreement with previous models of the thin filament based on EM and FRET data in which the arrowhead-shaped IT complex points towards the barbed end of the actin filament [10,24,25], but is in contrast to an earlier model based on single-particle analysis of reconstructed thin filament [11].…”
Section: Discussionsupporting
confidence: 90%
“…4 A and E), which is broadly consistent with a previous model for the skeletal muscle thin filament (Model 2 of Knowles et al) [12] and the recently published model of cardiac thin filament in the relaxed state using a single-particle reconstruction technique [23]. It is also in general agreement with previous models of the thin filament based on EM and FRET data in which the arrowhead-shaped IT complex points towards the barbed end of the actin filament [10,24,25], but is in contrast to an earlier model based on single-particle analysis of reconstructed thin filament [11].…”
Section: Discussionsupporting
confidence: 90%
“…The reconstructions revealed that the fragment competes with tropomyosin for a common site and fixes tropomyosin in the B-state position seen in low-Ca maps. Yang et al (229) later confirmed these results by reconstructing whole troponin on thin filaments. The work therefore directly connected troponin action to steric regulation.…”
Section: Structural Validation Of the Three-state Regulatory Modelsupporting
confidence: 55%
“…While noise reduction is advantageous, helical reconstruction is very tedious and cannot be easily used to categorize variants within a class of filaments or, as mentioned, to reconstruct nonhelically arranged thin-filament elements. To determine troponin structure, for example, different reconstruction methods are needed to recover troponin density contributions on actin-tropomyosin (174,175,229).…”
Section: D Reconstruction Of Thin Filamentsmentioning
confidence: 99%
“…The structure of the two TM-binding sites (green) is unknown, and a tentative model was generated based on secondary structure prediction and energy minimization (5). TM is shown in the blocked state, which it assumes when bound to the filament with Ca2þ-free troponin (53,111). Of note, this model is consistent with TM's ability to explore all three states on the filament (blocked, closed, and open) (53,54), without generating steric clashes with Tmod at the pointed end.…”
Section: Does Lmod Cap the Pointed End?mentioning
confidence: 99%